2013
DOI: 10.5665/sleep.2964
|View full text |Cite
|
Sign up to set email alerts
|

Cues of Fatigue: Effects of Sleep Deprivation on Facial Appearance

Abstract: The results show that sleep deprivation affects features relating to the eyes, mouth, and skin, and that these features function as cues of sleep loss to other people. Because these facial regions are important in the communication between humans, facial cues of sleep deprivation and fatigue may carry social consequences for the sleep deprived individual in everyday life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
163
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(180 citation statements)
references
References 20 publications
12
163
4
1
Order By: Relevance
“…There is some work that has shown that even among standardized photos, in which participants are asked to hold a neutral expression, raters were able to judge images of sleep deprived individuals as more fatigued and sadder than images of the same participants after a normal sleep [51]. Sleep deprived images were also said to have 'droopier mouths' and 'hanging eyelids'.…”
Section: (E) Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some work that has shown that even among standardized photos, in which participants are asked to hold a neutral expression, raters were able to judge images of sleep deprived individuals as more fatigued and sadder than images of the same participants after a normal sleep [51]. Sleep deprived images were also said to have 'droopier mouths' and 'hanging eyelids'.…”
Section: (E) Expressionmentioning
confidence: 99%
“…In 3D and 2D images, we have objectively measured variation in the upward or downward turn of the mouth as well as the extent to which eyes are opened (hereafter referred to as 'mouth curvature' and 'eye openness'). These particular facial features were selected for investigation because they are related to perceptions of sadness and fatigue [51] and may therefore also influence judgements of health. In Study 1, the contribution of mouth curvature, eye openness and measured facial adiposity are tested in health judgements of 3D faces.…”
Section: (F ) Summary and Future Directionsmentioning
confidence: 99%
“…We expected that sleep restriction would be associated with negative mood manifested in a more downturned mouth configuration, and increased tiredness manifested in reduced eyelid-openness (Sundelin et al, 2013). We further predicted that changes in these facial features would impact perceptions of intelligence.…”
Section: Study 4 -Sleep-restricted Facesmentioning
confidence: 99%
“…The other tasks are ones that humans often engage in as social animals. Previous work has shown that judgments of emotion (Ekman, 1973;Izard, 1971), fatigue (Sundelin et al, 2013), trustworthiness and attractiveness (Willis & Todorov, Fig. 1.…”
Section: Designmentioning
confidence: 99%